Cassava root chips and Moringa oleifera leaf meal as alternative feed ingredients in the layer ration - Tesfaye, E.B.; Animut, G.M.; Urge, M.L.; Dessie, Tadelle (Elsevier, 2014)
A study was conducted to evaluate effects of cassava root chips (CRC) and Moringa oleifera leaf meal (MOLM) inclusion in layer rations on egg laying performance, egg quality parameters, fertility, and hatchability. One hundred twenty Dominant CZ layers, 22 wk of age, and 12 cocks were used and equally divided into 4 dietary treatments with 3 replications. Treatment rations contained CRC and MOLM [i.e., T1 (0% CRC and 0% MOLM), T2 (50% CRC and 0% MOLM), T3 (0% CRC and 5% MOLM), and T4 (50% CRC and 5% MOLM)]. The CRC and MOLM were used to substitute for 100% corn grain and 5% soybean meal, respectively. Hens were weighed at the start and end of the experiment and BW change was calculated. Data on DM intake, hen-day egg production, egg weight, and egg mass were recorded daily. Egg quality parameters were determined at an interval of 15 d on 4 eggs per replicate. Fertility and hatchability of eggs, as well as mortality of birds and embryonic mortality of fertile eggs during the incubation period were recorded. From the chemical analysis, the calculated ME content of CRC was 3,852 kcal/kg of DM and the CP content of MOLM was 28%. The DM intake of birds, hen-day egg production, egg mass, FE, and mortality rate were not influenced by treatments. Body weight change and egg weight were higher for T4 as compared with other treatments. Most external and internal egg quality parameters, especially yolk color, were improved when the diet contained MOLM. Fertility showed nonsignificant differences among treatments. However, hatchability percentage for T1 was lower than the other treatments. In conclusion, CRC at 50% of the diet, CRC replacing corn grain 100%, or MOLM at 5% of the diet replacing soybean meal can impart similar or better positive effects on egg production, egg quality parameters, eggs fertility, and hatchability of Dominant CZ layers. Thus, 50% CRC, 5% MOLM, or a combination of both can successfully be used in the diet of layers as energy and protein feed ingredients, respectively.